The Implementation of Computer-Assisted Language Learning (CALL) in the EFL Setting: A Case Study in a Secondary School in Indonesia - Dwita Laksmita Rachmawati; Dian Fadhilawati; Slamet Setiawan (English Teaching Journal : A Journal of English Literature, Language and Education, 2020)
In this digital era, we cannot ignore that the use of Computer Assisted Language Learning (CALL) has given many benefits for both teachers and students in English instruction, especially in facilitating the students with an enjoyable and interesting learning experience. This research is a case study which aimed to investigate: 1) How is the implementation of CALL in the EFL setting, 2) How are the students’ attitude toward the use of CALL in English teaching and learning process, 3) How are the students’ achievement after the implementation of CALL in English teaching-learning process. The Subjects of this research were 30 students at SMA Laboratorium UM Malang. The data of this research were collected from the interview, observation checklist, questionnaire, and tests. The result of this research revealed that the implementation of CALL gave a positive effect on the students' achievement and broaden students' experience in learning English based on authentic context. Moreover, the students also presented positive responses toward the used of CALL in the English teaching-learning process.